Basic of morphological properties of gebeng bauxite - Siti Hajar, Aziz (2016)
Bauxite ore is a primary raw material required in aluminium production where its mining had been discovered at Gebeng in Kuantan district, Pahang. Bauxite collected will be export to manufacturing country, for example China to be process into aluminium. Basic properties of bauxite is determined for exporting purpose in which several international specifications need to be follow while handling bauxite in order to ensure those raw materials are passing the standard to be imported. IMSBC Code; an international standard for cargo transportation is referred and Geospec 3: Model Specification for Soil Testing is referred for laboratory testing. Laboratory test had been done to three bauxite samples taken from Gebeng mines and from stockpile to identify its basic properties; particle size distribution, moisture content, specific gravity and its morphological properties. Laboratory test involved are Hydrometer test, Small Pcyknometer test, Dry Sieve test and SEM test. From laboratory test done, the average value of moisture content is 22.65%, the value of specific gravity is not between the range of 1190 kg/m3 to 1389 kg/m3 and particle size distribution for lumps is less than 70% from total mass which means bauxite samples collected consists of fine particles more than lumps. Result from SEM test proves that there are bulky of fine particles attached to the bauxite. Referring to the IMSBC Code, it can be stated that bauxite sample collected from Gebeng mines does not qualify the standard as its basic properties is more than the standard value and therefore it is not suitable to be export. This is due to the presence of bulky fine particles which tend to absorb water more than granular particles that may lead to liquefaction to occur. Liquefaction during cargo transportation is high risk especially when there are strong current at the sea. In order to ensure the bauxite is passing the standard, beneficiation process may takes place where it include washing, wet screening and mechanical or manual sorting.